Rinsing effect of 60% bay leaf (Syzygium polyanthum wight) aqueous decoction in inhibiting the accumulation of dental plaque during fixed orthodontic treatment - Fitria Avriliyanti; Sri Suparwitri; Ananto Ali Alhasyimi (Dental Journal (Majalah Kedokteran Gigi), 2017)
Background: Fixed orthodontic appliance patients have a high risk to increasing plaque accumulation in tooth surface due to the presence of fixed appliance components. Using mouthwash with antibacterial agent from herbal material can control dental plaque accumulation. Bay leaf (BL) contains active compounds such as essential oil, tannin and flavonoid that have been known as an antibacterial agent. Purpose: The purpose of this study was to determine the effect of rinsing with 60% of BL aqueous decoction to the accumulation of dental plaque in fixed orthodontic appliance patients. Method: This research was an experimental clinical research with pretest and post-test control group design conducted on 20 subjects with age ranged between 18-25 years old. All subjects were undergoing the last stage (finishing) of fixed active orthodontic treatment. The subjects were instructed to rinse with 60% of BL aqueous decoction and 0.2% chlorhexidine as a control. Wash out period that needed between rinsing with 60% of BL aqueous decoction and rinsing with 0.2% chlorhexidine was 7 days. Each mouthwash used routinely for 7 days with same duration and intensity. Plaque scoring was measured before and after each treatment using Orthodontic Plaque Index (OPI). Result: One-way Anova test showed that there was a significant difference in the plaque index before and after treatment between the group of rinsing with 60% of BL aqueous decoction and group of rinsing with chlorhexidine (p<0.05). Conclusion: Rinsing with 60% BL aqueous decoction can decrease the accumulation of dental plaque in fixed orthodontic appliance patients.